The Quantity and Biochemical Composition of Sap Collected from Silver Birch (Betula pendula Roth) Trees Growing in Different Soils - Justas Mingaila (Forests, 2020)
Birch sap is colourless or slightly opalescent and is traditionally drunk in spring. Currently, birch sap is becoming more important in the market sector as well as to pharmacy companies due to its biochemical composition and use in a wide variety of products. To extract good quality sap using birch resources in a sustainable way, there is a need to investigate the influence of the dendrometric parameters of birch trees and soil properties on the quantity and chemical composition of birch sap. This study is performed in five silver birch (Betula pendula Roth) forest stands growing in Histosol, Luvisol and Arenosol with different moisture and nutrient contents. The results indicated that the most productive silver birch trees for sap harvesting were taller than 28 m, had a diameter at breast height over 40 cm and a crown base height greater than 19 m. Additionally, the highest quantity of birch sap was harvested from trees growing in well-aerated mineral soils (Arenosol and Luvisol) with normal moisture content. However, the sweetest birch sap was harvested from trees growing in nutrient-rich organic (undrained peatland Histosol) and temporarily flooded mineral (Luvisol) soils.